The Semantic Web, Universalist Ambition and Some Lessons from Librarianship - Terrence A. Brooks (Information Research: An International Electronic Journal)
Building the semantic web encounters problems similar to building large bibliographic systems. The experience of librarianship in controlling large, heterogeneous collections of bibliographic data suggests that the real obstacles facing a semantic web will be logical and textual, not mechanical. Three issues are explored in this essay: development of a standard container of information, desirability of standardizing the information hosted by this standardized container, and auxiliary tools to aid users find information. Value spaces are suggested as a solution, but dismissed as impracticable. The standardization necessary for the success of the Semantic Web may not be achievable in the Web environment.